Development of decision support system to enhance the decision of rice pesticide management in paddy cultivation - Hairani, Saiful Ramadzan; Sidi, Fatimah; Ooi, Seng Tatt; Ishak, Iskandar; Affendey, Lilly Suriani; Mazlan, Norida (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Decision Support System (DSS) is defined as interactive computer-based systems that help decisions makers utilize data and models to solve problems [1]. The lack of adequate information on pesticides hinders users in making the correct and suitable decision on choosing the pesticides for specific pests. This paper describes the development of a decision support system that helps users to choose the suitable pesticide to eradicate pests in paddy cultivation. This system provides details information about the paddy cultivation in Malaysia such as the type of pests, symptoms, and type of pesticides, weather and the granary area in Malaysia. This DSS is very important to users like farmers because it can provide details of information about the paddy and on how to manage the application of pesticide.